Batuan Karbonat dan Pemanfaatannya di Dunia Industri - Isman Saleh (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
Carbonate rocks are one of the most important geological resources with a significant role in various industrial sectors, particularly as the main raw material in cement, lime, and construction industries. This study aims to review the characteristics, quality, and industrial potential of three major carbonate rock types—limestone, dolomite, and marble—based on relevant scientific literature. The research employed a literature review method using a qualitative-descriptive approach through analysis and synthesis of previous studies. Data were collected from scientific publications addressing the mineralogical, chemical, and physical aspects of carbonate rocks and their implications for industrial performance. The findings indicate that the quality of carbonate rocks is largely determined by mineral composition (calcite and dolomite), chemical purity (CaO and MgO), and the presence of impurities such as silica, alumina, and iron oxides. High-purity limestone rich in calcite is identified as the most efficient raw material for cement and lime industries due to its stable processing behavior and lower energy requirements. Conversely, dolomite with high magnesium content requires process adjustments to prevent excessive MgO formation during calcination. Marble, both in natural and waste powder form, shows promising potential as a supplementary material in sustainable cement production. Overall, this study emphasizes that understanding the mineralogical and chemical variations of carbonate rocks is essential for optimizing their processing strategies and promoting sustainable industrial utilization